Examination of Socio-Demographic Attributes and Body Mass Indices of Individuals with Disabilities - Birimoğlu Okuyan, Canan; Kerkez, Müjde (My University, 2025)
Introduction: Sociodemographic characteristics and disability have a significant impact on body mass index and are crucial for improving health outcomes in this population. Aim: The purpose of this study was to investigate the associations between sociodemographic factors and body mass index in children and people with disabilities. Methods: The descriptive study's sample consisted of impaired children who were registered at a disability center (n = 64). The research data were obtained face-to-face between March and July 2024 using a questionnaire form that included sociodemographic information as well as information on specific nutritional parameters. In addition to descriptive statistics, the Mann-Whitney U test and correlation analysis were performed to assess the research findings. Results: A total of 54.1% of the impaired individuals acquired their disability due to a traumatic event during the perinatal period, and 64.9% of the disabled individuals were male.. Additionally, 62.2% were partially dependent on daily activities, while 45.9% spent 3-4 hours per day in front of a screen. The body mass index (BMI) was 25.38 ± 5.17 for females, 22.00 ± 5.81 for males, and 25.82 ± 7.42 for adults. A significant positive correlation was observed between the commonly consumed foods of impaired children and their overall diet. In contrast, a negative correlation was found between their sleep duration and the foods they routinely consumed (r = 0.544, p = 0.002; r = -0.385, p = 0.039). Conclusion: The study discovered that the frequency of moderate obesity and obesity among people with impaired people was quite low. The study's findings highlight the need to improve impaired children's sleep length and eating habits.
Keywords: Obesity; Anthropometry; body mass index; demography; public health.